Caspian Region in the System of International Regions - Kosov Gennadiy Vladimirovich; Litvishko Olga Mikhaylovna (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения, 2015)
The given research paper presents an attempt to analyze the Caspian region from the point of view of its cross-border specifics. In contrast to the traditional understanding of the Caspian region as the region of heightened geopolitical significance the authors analyze its peculiarities and potential in the context of the cross-border cooperation dynamics. It is especially emphasized that the Caspian region may be considered as a cross-border region which, despite the substantial similarities is different from international transnational regions.